Some properties of intermetallic compounds of Sn with noble metals relevant for hydrogen electrocatalysis - Pinto, L. M. C. [UNESP]; Juarez, M. F.; Angelo, A. C. D. [UNESP]; Schmickler, W. (Elsevier B.V., 2014)
Using density functional theory and a model developed in our own group, we have investigated the suitability of three intermetallic compounds - AuSn, PdSn, and PtSn - as electrode materials for hydrogen oxidation in fuel cells, focusing on their CO tolerance and their catalytic properties. All three metals were found to have lower susceptibility to be poisoned by CO compared to platinum, but only PtSn promises to be a good catalyst for hydrogen oxidation. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon monoxide; Hydrogen catalysis; Intermetallic compounds